An Analysis on Slang Words in 8 Mile Movie: A Sociolinguistics Study - Igo Bani Christian; Putu Chrisma Dewi; Km Tri Sutrisna Agustia (LPPM Universitas Dhyana Pura, 2023)
Slang is an informal language as the outcome of the relationship between language and society. This study aims to analyze the types and the function of slang words in sociolinguistics view found in the 8 Mile movie. The theory used in this study is Wardhaugh (1986) and Alan & Burridge (2006). Classifying the slang words into five type and identifying the function into three function of slang words. The method used to conduct and collect data was descriptive qualitative method research, using observation and documentation methods. The analysis results from the study are consist of; the first of which is the types of slang words found consisting of fresh and creative slang words, clipping slang words, acronym slang words, flippant slang words, and imitative slang words. The second is function of slang words founded is consist of slang to initiate a conversation, slang to address person, slang to humiliate person. It can be concluded that the most type of slang found is clipping and function used to humiliate a person.